Transient Global Amnesia in a Patient Presenting with Hypertensive Emergency; a Case Report - Obara, Takafumi (Arch Acad Emerg Med, 2020)
Transient global amnesia (TGA) is characterized by the abrupt onset of global amnesia, particularly anterograde amnesia. The pathophysiology of TGA is poorly understood and it could be caused by various factors and be associated with various diseases. We report a 58-year-old man who presented to the local emergency room with TGA lasting for several hours. The patient had complete anterograde amnesia without a past medical history of migraine or neurological findings. His systolic blood pressure on presentation was 220 mmHg, which was immediately treated with intravenous calcium ion influx inhibitor. Other than global amnesia, there was no evidence of neurological disturbance. Computed tomography and magnetic resonance imaging results were unremarkable. After treatment of his hypertension, his amnesia resolved within 12 hours. Emergency department physicians may encounter TGA. Correct diagnosis of the condition depends on recognizing the disease.